Analisis library anxiety pada mahasiswa di Perpustakaan UIN Sunan Gunung Djati Bandung - Rizal Mohamad Sihabudin (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study aims to analyze the level of library anxiety, identify the influencing factors, and formulate relevant mitigation strategies at the Library of UIN Sunan Gunung Djati Bandung. The research employed a quantitative descriptive method with a survey approach, involving undergraduate students from the 2024 cohort as the study population. The instrument used was the AQAK Library Anxiety Scale V2. The results indicate that the overall level of library anxiety among students falls into the low-anxiety category. However, several dimensions show higher mean scores, categorized as mild anxiety, namely Information, Communication, and Technology (ICT), Library Resources and Services, and Information Literacy. These findings suggest that students still experience anxiety related to the use of digital technology, limited information literacy skills, and difficulties in utilizing library resources. Recommended mitigation strategies include strengthening user education programs, conducting more proactive promotion of library services and resources, and upgrading infrastructure, particularly those related to the use of information and communication technology.